PDPN+ cancer‐associated fibroblasts enhance gastric cancer angiogenesis via AKT/NF‐κB activation and the CCL2‐ACKR1 axis - Zhenxiong Zhao; Hui Sun; Yingxue Liu; Yanqiu Zhang; Xin Wang; Xu Wang; Cong Tan; Shujuan Ni; Weiwei Weng; Meng Zhang; Lei Wang; Dan Huang; et al. (MedComm)
Abstract Cancer‐associated fibroblasts (CAFs) are intrinsic components of the tumor microenvironment that promote cancer progression and metastasis. Through an unbiased integrated analysis of gastric tumor grade and stage, we identified a subset of proangiogenic CAFs characterized by high podoplanin (PDPN) expression, which are significantly enriched in metastatic lesions and secrete chemokine (CC‐motif) ligand 2 (CCL2). Mechanistically, PDPN(+) CAFs enhance angiogenesis by activating the AKT/NF‐κB signaling pathway. The canonical NF‐κB signaling protein P65 binds to the promoter region of CCL2, inducing its expression. Additionally, we found that CCL2 interacts with its nonclassical receptor ACKR1 (expressed on endothelial cells) to exert its proangiogenic effects. Furthermore, the disruption of CCL2‐ACKR1 communication via a CCL2 neutralizing antibody or the inhibition of AKT signaling transduction using AKT inhibitors effectively suppressed tumor growth. Together, this study elucidates the mechanism by which PDPN(+) CAFs promote angiogenesis, providing a deeper understanding of the molecular processes underlying CAF‐mediated angiogenesis and suggesting potential therapeutic targets for gastric cancer treatment.